PENINGKATAN KETERAMPILAN LONCAT KANGKANG MELALUI PERMAINAN SISWA KELAS 4 SD NEGERI KIDAL KABUPATEN MALANG - Saputra, Lulut Gilang; Tushawandi, Tushawandi (Gelanggang Pendidikan Jasmani Indonesia, 2024)
Objective: This research aims to improve straddle jumping agility gymnastics skills through games. Method: The research design is action research which was carried out in two cycles consisting of planning, implementation, observation and reflection in each cycle, the number of research subjects was 32 class IV students at SD Negeri Kidal, Malang Regency. Data collection techniques include observation and field notes. The data analysis technique in this research uses quantitative analysis techniques in the form of numbers and percentages. Results: In cycle I, the average score obtained by students after performing the straddle jump movement was 74,85 with a completion percentage of 56.25%, in cycle II there was an increase with the average score obtained by students of 81,55 with a learning completion percentage of 81.25%.  So that the application of the game can improve the straddle jumping agility gymnastics skills of fourth grade students at SD Negeri Kidal, Malang Regency.